ETNOBOTANI MASYARAKAT BUGIS DI DESA LEMPE KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Andi Muraqmi; Syariful Anam; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2015)
Lempe village is occupied by various tribes among of them is Buginese, Dampal tribe, and Mandarese tribe, but In quantitative terms Buginese societyis constitute the majorityin the village Lempe which until now is still utilizing plants to meet their daily needs. The objectives of study were to determine the diversity of plants utilized by the Buginese for daily needs, such as food, clothing, shelter, medicine, ritual customs and others. The research has been caryed out from September to October 2014 through interviews with respondents, basedon Pieronietal, (2002). Interview used was semi-structured. The data obtained in the field were analyzed descriptively with a quantitative approach using equation Index of Culture Significance/ ICS (Turner, 1988). The results showed that there were 106 plant species used by Buginese society in the study site for their daily needs. Plants that have the highest ICS was